Bioengineered Materials for Skull Base Reconstruction—Current Clinical Applications: Systematic Review and Meta-analysis - Gago, Guilherme; Comeau, Marc-Olivier; Ness, Rodrigo; Gomes, Fernando; Gibbon, Frederico de Lima; Champagne, Pierre-Olivier (Journal of Neurological Surgery Part B: Skull Base, 2025)
Skull base reconstruction (SBR) is a crucial aspect of open and endoscopic skull base surgery. Currently, multilayer reconstruction with vascularized tissues is the standard technique. Despite advancements, complications such as postoperative cerebrospinal fluid leaks (PO-CSF-L) and infections persist. Bioengineered materials (BEM) have emerged for SBR, showing promising results.A systematic review was conducted using Embase, PubMed, Scopus, and Cochrane databases. We performed a proportional meta-analysis of studies utilizing BEM for SBR and a comparative analysis with control groups that underwent SBR without biomaterials. The odds ratio assessed treatment effects for binary outcomes.From 1,075 potential articles, 14 met the inclusion criteria. Five BEM were identified: hydroxyapatite (HXA), leukocyte–platelet-rich fibrin (L-PFR), collagen matrix (CM), polyglycolic acid (PGA), and porous polyethylene (PP). The analysis included 1,960 patients, with 1,570 in experimental groups using BEM. Pooled data indicated a PO-CSF-L proportion of 0.02% (95% CI: 0.01–0.03%), postoperative CSF diversion (PO-CSF-d) at 0.01% (95% CI: 0.00–0.04), and PO infection at 0.02% (95% CI: 0.00–0.05%). Common effect models showed that CM had a lower total PO infection rate (0.01; 95% CI: 0.00–0.01, p = 0.0006) compared with HXA (0.08; 95% CI: 0.05–0.11, p = 0.0007). Comparative analysis demonstrated lower odds of PO-CSF-L (OR 0.37; 95% CI: 0.15–0.89, p = 0.026) and infections (OR 0.47; 95% CI: 0.13–1.47, p = 0.264) in patients with BEM.Our results indicate that bioengineered materials are viable for skull base reconstruction, associated with low rates of postoperative CSF leaks, diversions, and infections.
Keywords: bioengineered materials; skull base reconstruction; CSF leak; infection; meta-analysis